2022
DOI: 10.47509/jafe.2022.v03i01.01
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Review of Implications of Financial Leverage on Performance of Quoted Oil and Gas Companies in Nigeria

Abstract: This study was conducted to examine the implication of financial leverage on performance of quoted oil and gas companies in Nigeria. This is premeditated on the fact that debt capital is usually acquired by firm to finance assets with the expectation the returns from such investments will exceed the costs of the debt capital used. Often, this is always not the case either because of inappropriate management strategies or other reasons. Ex-post-facto research design was adopted involving use of panel secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This could be because when firms are more profitable, they have greater resources to invest in systems, processes, and controls that can improve the quality of their risk management and disclosure practices. The outcome of this finding was supported by the works of Okpala et al (2021) and Etim et al, (2023) who observed a positive relationship between profitability and risk management disclosure.…”
Section: Discussion Of Findingssupporting
confidence: 55%
See 2 more Smart Citations
“…This could be because when firms are more profitable, they have greater resources to invest in systems, processes, and controls that can improve the quality of their risk management and disclosure practices. The outcome of this finding was supported by the works of Okpala et al (2021) and Etim et al, (2023) who observed a positive relationship between profitability and risk management disclosure.…”
Section: Discussion Of Findingssupporting
confidence: 55%
“…And market risk disclosure has a significant positive effect on earnings multiple of listed construction/real estate firms in Nigeria. Etim et al, (2023) examined the relationship between the firm's characteristics and asset growth. Ex post facto sourcing of data was conducted from the annual financial reports of relevant companies on the Nigerian Stock Exchange from 2008 to 2019 fiscal years.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation